Ayurvedic Intervention in Atypical Eczema Progression (AYUSHDHARA, 2025)
Eczema is a chronic, relapsing inflammatory skin disorder. Long-term corticosteroid therapy often leads to drug dependency and reduced efficacy. This case report highlights a rare progression of Vicharchika (eczema) into erythroderma (moderate severity), necessitating a deviation from conventional Ayurvedic treatment approaches. Clinical Findings: A 40-year-old female patient presented with a chronic 8-year history of eczema involving the hands and feet, with overuse of corticosteroids. Upon initiation of Snehana karma (oleation), her condition rapidly deteriorated, manifesting as erythroderma with widespread erythema, foul-smelling pus oozing, epidermal shedding, malaise, and systemic distress. Intervention: Initial Snehana was given for 1 day but withdrawn after aggravation. The revised approach excluded Shodhana due to the patient’s unsuitability and incorporated Parisheka (local irrigation therapy) and Oral medications. Results: Clinical monitoring using Visual Analog Scale (VAS) and Numerical Rating Scale (NRS) revealed significant symptom improvement from peak values (VAS 9, NRS 7) to minimal values. Conclusion: The successful resolution of erythroderma demonstrates the efficacy of tailored Shamana (palliative) medicine and external therapy.